The role of compatibility in long-term action-effect binding and effect memory. - Schreiner, Marcel R.; Mocke, Viola; Kunde, Wilfried (Memory & Cognition, 2026)
Through interactions with our environment, we cause perceivable effects. In four experiments, we investigated long-term bindings between action and effect features in action-effect episodes, and how they are influenced by action-effect compatibility (AEC). In addition, we asked whether AEC facilitates memory for effects. In a prime phase, participants performed actions that resulted in an effect that comprised two features, namely a spatial feature (a linear movement or rotation of a box in a certain direction) and a certain identity of a word presented in that box. The effect movement or rotation was either spatially compatible or incompatible (or neutral, in Experiment 3) to the action. In a subsequent probe phase, we assessed whether participants were inclined to repeat the action when re-presented with the effect word. Memory for effect words was also tested. Results showed a higher propensity to repeat an action in Experiments 1–3, but not when the influence of spatial effect features was reduced (Experiment 4). Participants further tended to retrieve the spatial effect location in the neutral condition to a similar extent to in the compatible and incompatible condition in Experiment 3. These findings suggest long-term feature bindings after one-shot learning of action-effect episodes, although primarily due to bindings between different effect features rather than between action and effect features. AEC facilitated memory for effect words in a free recall test (Experiment 1) given repeated presentation of the effect word, but not in a recognition test (Experiments 2–4). Theoretical implications of these findings are discussed.